Feces of Finisher Pigs Have a Low Prevalence of Shiga Toxin-Producing Escherichia coli that are of Public Health Importance - R. G. Amachawadi; X. Shi; J. Bai; M. D. Tokach; J. C. Woodworth; S. S. Dritz; J. M. DeRouchey; R. D. Goodband; T. G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 2020)
Shiga toxin-producingEscherichia coli(STEC) are major food pathogens that cause mild to bloody diarrhea, including complications of kidney damage and even death, particularly in children and elderly. Seven serogroups of STEC, O26, O45, O103, O111, O121, O145, and O157, called top-7 STEC, are responsible for the majority of STEC infections in the US. Shiga toxins, which are proteins secreted by the bacteria, are major virulence factors contributing to the disease. There are two Shiga toxin types, 1 and 2, encodedstx1 andstx2 gene, respectively and each type has several subtypes. Another major virulence factor, intimin, a protein on the bacterial cell surface encoded by theeaegene, mediates attachment of the bacterial cell to the intestinal epithelial cells. The severity of STEC infections in humans is dependent on the Shiga toxin type and subtype. Cattle are a major reservoir of STEC and carry the bacteria in the hindgut and shed them in the feces, which is a source of contamination of food and water. Swine have also been shown to harbor STEC in the gut and shed in the feces, and a few outbreaks of STEC infections in humans have been linked to pork and pork products. The STEC does not cause infections in cattle, but in swine, particularly in weaned piglets, it causes edema disease. We conducted a study that utilized molecular (polymerase chain reaction [PCR]) and culture methods to determine prevalence and characteristics of top-7 STEC in the feces of finisher pigs collected from ten pig flows in eight states. A total of 598 fecal samples were collected and analyzed. The overall prevalence of Shiga toxin genes,stx1 orstx2, was 70.1%, andeaewas detected in 66.7% of the samples. Based on the PCR method, among the top-7 STEC, O26 (14.4%), O121 (22.9%) and O157 (18.5%) were the predominant serogroups detected. None of theE. coliO157 isolated, a serogroup implicated in pork-linked outbreaks, contained Shiga toxin genes. Although a number of fecal samples were positive for the top-7 STEC serogroups, culture method identified one strain each ofstx1-positive O26 (0.2%) and O103 (0.2%), and 23 strains ofstx2-positive O121 (3.9%). Serogroups O26 and O103 possessedstx1a subtype andeae, which have the potential to cause serious infections in humans. Serogroup O121 carried thestx2e subtype, which is involved in causing edema disease in swine and rarely implicated in human infections. Our results indicated that finisher pig feces contain a high prevalence of top-7E. coliserogroups, but prevalence of top-7 serogroups that have the ability to produce Shiga toxins was low. In conclusion, a majority of STEC shed in the feces of swine are not of major public health importance.
Keywords: E. coli serogroups; real-time PCR; culture approach; finisher pigs